Acercamiento etimológico al cast. (gall.-port.) buscar: lat. poscere - Anguita Jaen, Jose Maria (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
The purpose of this article is to propose an etymological relationship between cast. (gal.-port.) buscar and lat. poscere ‘to ask for’. From a semantic point of view, since both verbs imply a privative opposition of terms meaning ‘to try to obtain’ (cast. buscar-pedir; lat. quaerere-petere-poscere), closely related with the verbs of volition (cast. querer, lat. uelle), the loss of uelle in castilian and the choice of quaerere to take its place could have caused the meaning of the ‘to try to obtain’ verbs to change, and, more specifically, the verb poscere to stop meaning ‘to ask for’ in order to mean ‘to look for’. The final form sprang from the mutual interference of the first persons of the simple present of poscere (posco) and of a verb imported from Europe into the north-western section of the Iberian Peninsula in the 11th century, boscare-buscare (bosco-busco), which meant ‘to do something in the forest’.